2005
DOI: 10.1007/s00436-005-1418-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of serum antibody to Entameba histolytica in various population samples of amebic infection using an enzyme-linked immunosorbent assay

Abstract: Microscopic identification of Entameba histolytica in stool is insensitive to differentiate this pathogenic ameba from morphologically identical Entameba dispar. An enzyme-linked immunosorbent assay method was applied for diagnosing amebiasis by detection of E. histolytica antibody. A total of 258 sample sera were analyzed from five different groups including amebiasis patients, E. histolytica/E. dispar asymptomatic cyst carriers, patients clinically presumed to have intestinal and extra-intestinal amebiasis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…dispar. By use of an enzyme-linked immunosorbent assay-based test, it was more recently shown that just 8 of the 51 (15.6%) asymptomatic amebic cyst passers examined had anti-E. histolytica antibodies, supporting the hypothesis that E. dispar is more prevalent in asymptomatic cyst passers in this country (7).…”
mentioning
confidence: 80%
“…dispar. By use of an enzyme-linked immunosorbent assay-based test, it was more recently shown that just 8 of the 51 (15.6%) asymptomatic amebic cyst passers examined had anti-E. histolytica antibodies, supporting the hypothesis that E. dispar is more prevalent in asymptomatic cyst passers in this country (7).…”
mentioning
confidence: 80%
“…A partir del crecimiento que presentaron los hibridomas en las placas después de la clonación y reclonación se seleccionó el clon 3G8C3 secretor del anticuerpo monoclonal anti EhCP5r para la expansión in vitro e in vivo, (20)(21)(22)(23)(24).…”
Section: Resultsunclassified
“…E. dispar has been shown to be 14.5 times more common than E. histolytica by the ELISA method, the only method that can definitively differentiate E. histolytica and E. dispar [7,24]. The more recent method of the detection of fecal antigens by ELISA is an alternative to microscopy, and the gold standard, with sensitivity and specificity over 95% [24,25]. In Sweden, 165 of 207 patients microscopically diagnosed with E. histolytica/E.…”
Section: Discussionmentioning
confidence: 98%